Socio-demographic, Clinical and Laboratory Characteristics of Melioidosis: Four-Year Experience of Managing Consecutive 11 Cases in a Tertiary Care Hospital of Bangladesh (BIRDEM Medical Journal, 2017)
Background: Melioidosis is caused by Burkholderia pseudomallei, a gram negative non-fermentative bacillus found in water and soil. Transmission to human is by contact and it causes disease mostly in the immunocompromised state. As melioidosis closely mimics tuberculosis it is often misdiagnosed and often empirically treated as tuberculosis. Increasing numbers of published cases among Bangladeshis and isolation of B. pseudomallei in the soil of Gazipur district has confirmed our country as a definite country for melioidosis.Methods: This study was carried out in the Department of Medicine, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, Bangladesh from September 2013 to September 2016. Adult patients with melioidosis confirmed by growth of B. pseudomallei from different specimens were included. Socio-demographic, clinical and laboratory characteristics were studied and treatment outcome was also documented.Results: Total 11 cases including 9 males were detected with melioidosis during the study period. All cases were diabetic. Mean age was 39.73 years. Eight cases were classified as endemic while 3 patients returned from overseas. Four patients (36.36%) home district was Tangail. Common presentations were fever (100%), cough (45.45%), dysuria (36.36%), cutaneous lesions (36.36 %) and septic shock (36.36%). The common sites involved were skin (36.36%), genitourinary tract (36.36%) and lung (36.36%) followed by joint (18.18%). Ten cases (90.9%) had neutrophilic leucocytosis with raised ESR/CRP in all cases. Culture of sixteen different specimens revealed growth of B. pseudomallei. In 6 a cases co-trimoxazole resistance was found in vitro. Common radiological findings showed lung involvement (36.36%) and organ abscess (18.18%). One patient was lost from follow up following discharge. Among the remaining 10 patients, 6 were declared cured, 1 patient improved and 3 patients died from septic shock. Ceftazidime/meropenem as initial therapy followed by a combination of doxycycline and trimethoprim-sulfamethoxazole or doxycycline and amoxicillin-clavulanic acid proved to be effective.Conclusion: Observation revealed that this disease, if remained untreated, can cause life threatening complications, even death. Therefore, suspicion of melioidosis should be considered in appropriate clinical scenario.Birdem Med J 2017; 7(1): 28-37